Reducing Students’ Anxiety in Speaking English through Cooperative Learning (Make A Match Type) - Anshar, Asmita; Ariyani, Amra; Fauzan, Muhammad Miftah (Journal of Excellence in English Language Education, 2024)
This research aims to determine whether cooperative learning (make-a-match type) reduces students' anxiety about speaking English. The research utilized a pre-experimental method with a total sample of 23 students from class X MPLB at SMKN 4 Selayar, employing a cluster random sampling technique. Data collection involved administering a pre-questionnaire, applying the treatment, and then conducting a post-questionnaire. The data analysis results indicate that cooperative learning (make a match type) effectively reduces students’ anxiety in speaking English. This is supported by the t-test value, where Sig. (2-tailed) = 0.00, which is less than the significance level of 0.05. Therefore, H0 is rejected and H1 is accepted. Consequently, it can be concluded that cooperative learning (make-a-match type) alleviates students' anxiety in speaking English. This research contributes to enhancing the English language teaching process by implementing cooperative learning (make-a-match type), aimed at reducing students' speaking anxiety.